Peran Media Sosial Dalam Membentuk Akhlakuk Karimah Remaja - Erwan Efendi; T.M. Rafdiansyah (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to determine the role of social media in building adolescent akhlakul karimah. This is considering that teenagers in Indonesia have experienced a decline in terms of akhlakul karimah. With the decline in the morals of these teenagers, the community becomes uncomfortable with the behavior of these teenagers. The method in this study used qualitative data collection techniques using interview and observation techniques. The results of this study are that the role of social media in shaping adolescent akhlakul karimah is very important in order to create community comfort. With information about akhlakul karimah posted on social media it is able to create a harmonious life between communities and prevent misunderstandings from occurring that cause commotion in the environment. Keywords: social media, noble character, youth